2020
DOI: 10.1007/s11701-020-01057-8
|View full text |Cite
|
Sign up to set email alerts
|

From Da Vinci Si to Da Vinci Xi: realistic times in draping and docking the robot

Abstract: Robot-assisted surgery is assumed to be time consuming partially due to extra time needed in preparing the robot. The objective of this study was to give realistic times in Da Vinci Xi draping and docking and to analyse the learning curve in the transition from the Si to the Xi in an experienced team. This prospective study was held in a hospital with a high volume of robot-assisted surgery in general surgery, urology and gynaecology. Times from the moment patients entered the operating room until the surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…In theory, the Xi system has been optimized, and the robotic arms have more joints, which should allow the surgeons to operate more smoothly, thus shortening the patients' time in the operating room. Schans et al [ 10 ] compared 18 cases of partial nephrectomy with the Xi system and 18 cases of partial nephrectomy with the Si system and found that the docking time of the Xi system was significantly shorter than that of the Si system. Similar results have been demonstrated in a study of robot-assisted laparoscopic adrenalectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the Xi system has been optimized, and the robotic arms have more joints, which should allow the surgeons to operate more smoothly, thus shortening the patients' time in the operating room. Schans et al [ 10 ] compared 18 cases of partial nephrectomy with the Xi system and 18 cases of partial nephrectomy with the Si system and found that the docking time of the Xi system was significantly shorter than that of the Si system. Similar results have been demonstrated in a study of robot-assisted laparoscopic adrenalectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improved RCS technological development and a transition from DaVinci Si ® to the Xi ® model, and a dedicated robotic team can reduce total operation time. Several studies have confirmed a reduction in both docking and total operating times using the DaVinci Xi ® model, with an average of 21 cases needed to reach a statistically significant reduction in the docking time [ 34 – 36 ]. The technological development of RCS and the da Vinci Xi ® model’s introduction allows the surgeon more freedom and the ability to perform even technically demanding procedures that previously have been difficult to perform laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…This ease of docking the SP robot addresses complaints surrounding extended set-up times with multiarm robotic systems in the past. 22 The SP robot consists of a "C-arm" which provides 360-degree rotation both around the remote center of the cannula and within the instrument port, which we have found to be immensely useful for transanal robotic surgery. This rotation allows visualization of all quadrants of the rectum without the need for repositioning or redocking of the robot.…”
Section: Evolution Of Transanal Surgery For Rectal Cancermentioning
confidence: 99%